Inclusion of Diverse Learners in the Educational System: AEC487/WC150, 7/2013 - Rubenstein, Eric D.; Thoron, Andrew C. (EDIS, 2013)
Every student in the United States has the right to an education. But not every student is ready, prepared, or willing to learn. Teachers trying to fully engage students in the learning environment can find it difficult when working with students from diverse backgrounds. Forms of diversity such as socioeconomic status, ethnicity/race, learning style, cognitive ability, gender, and ability to process and store knowledge can cause an “achievement gap” between students. This 4-page fact sheet highlights effective educational strategies for engaging students in the learning environment and assisting in closing achievement gaps. Written by Eric D. Rubenstein and Andrew C. Thoron and published by the UF Department of Agricultural Education and Communication, July 2013. http://edis.ifas.ufl.edu/wc150